One-step hydrothermal synthesis of nitrogen-doped carbon dots as a super selective and sensitive probe for sensing metronidazole in multiple samples. Issue 39 (21st September 2021) - Du, Jinyan; Wang, Chaofeng; Yuan, Pingchuan; Shu, Qin; Xu, Na; Yang, Ying; Qi, Shuangqing; Ye, Yin; Zhu, Changqing
Abstract : Using fluorescence quenching of N-CDs with bright blue emission, a new sensing nanoplatform was constructed for the successful detection of metronidazole in real samples. Abstract : A reliable, super selective and sensitive nitrogen-doped carbon dots (N-CDs) nanoprobe that can quantitatively and quickly detect the concentration of metronidazole (MTZ) in multiple samples was built. We first prepared the N-CDs using N -(3-dimethylaminopropyl)- N ′-ethylcarbodiimide hydrochloride (EDC·HCl) as the precursor via a green, facile one-step hydrothermal method. The as-synthesized N-CDs were characterized by a variety of analytical and spectroscopic techniques, which revealed excitation-dependent fluorescence behavior with the maximum excitation and emission wavelengths being 335 and 370 nm, respectively. Significantly, the fluorescence emission of N-CDs underwent initial quenching upon the addition of MTZ via the inner filter effect (IFE), indicating a prospective detection method for MTZ. The linear range for MTZ detection was 0.1–250 μM, and the corresponding limit of detection (LOD) and limit of quantification (LOQ) were calculated to be only 70 nM and 233.33 nM, respectively. Moreover, due to the negligible cytotoxicity and superior biocompatibility, the fabricated N-CDs show a promising prospect for detecting MTZ in living cells. In general, our proposed N-CDs-based fluorescence sensing platform possesses super low LOD and LOQ values, wide linear range, and satisfactory selectivity, and can be applied to the detection of MTZ in multiple real samples.